2022
DOI: 10.1021/acs.jmedchem.2c01004
|View full text |Cite
|
Sign up to set email alerts
|

Fragment Libraries Designed to Be Functionally Diverse Recover Protein Binding Information More Efficiently Than Standard Structurally Diverse Libraries

Abstract: Current fragment-based drug design relies on the efficient exploration of chemical space by using structurally diverse libraries of small fragments. However, structurally dissimilar compounds can exploit the same interactions and thus be functionally similar. Using three-dimensional structures of many fragments bound to multiple targets, we examined if a better strategy for selecting fragments for screening libraries exists. We show that structurally diverse fragments can be described as functionally redundant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The diversity of chemical structures, however, does not presage the ability to provide hits for different proteins, as structurally dissimilar fragments may exhibit the same biological activity. XChem's analysis of DSiP screening campaigns thus demonstrated that structurally dissimilar fragments can form the same interactions, consistent with the pharmacophore concept (Carbery et al, 2022). The investigation of 309 proteinfragment structures obtained for 10 unrelated targets and 225 fragments led the authors to propose a strategy for selecting functionally diverse fragments based on the interactions formed with multiple proteins, as encoded in interaction fingerprints.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The diversity of chemical structures, however, does not presage the ability to provide hits for different proteins, as structurally dissimilar fragments may exhibit the same biological activity. XChem's analysis of DSiP screening campaigns thus demonstrated that structurally dissimilar fragments can form the same interactions, consistent with the pharmacophore concept (Carbery et al, 2022). The investigation of 309 proteinfragment structures obtained for 10 unrelated targets and 225 fragments led the authors to propose a strategy for selecting functionally diverse fragments based on the interactions formed with multiple proteins, as encoded in interaction fingerprints.…”
Section: Introductionmentioning
confidence: 62%
“…A minimal molecular weight around 175 Da was suggested by the study of the conservation of the binding mode of the fragments in their drug-like superstructures (Jacquemard and Kellenberger, 2019). The same threshold was proposed following the analysis of XChem's screening campaigns which revealed that fragments that have never been shown to bind to a target tend to have a low molecular weight compared to fragments that bind to one or more targets (Carbery et al, 2022). According to the size criterion, about half of the versatile PDB fragments may provide a valid base for fragment growing (105 fragments with MW > 175 Da).…”
Section: Resultsmentioning
confidence: 99%
“…This is a particularly useful finding given that recent research into fragment screen libraries has highlighted that even screens designed to be diverse structurally offer a limited exploration of protein pockets. 43…”
Section: Resultsmentioning
confidence: 99%
“…The predicted interactions were compared with those of the parent fragments to discern whether the merge is able to replicate unique interactions made by each of the fragments (representing useful merges). In addition to comparing chemical diversity of the compound sets, we also compared functional diversity by looking at the interactions made by each compound set; the analysis adapts the methodology described in [57]. Interaction diversity was analysed for each target by selecting the minimal subset of filtered compounds that represent all possible interactions (compounds are ranked according to the amount of ‘information’ recovered and are added until reaching a final set in which all possible interactions are recovered).…”
Section: Methodsmentioning
confidence: 99%